The Influence of Environmental Knowledge, Consumer Habits, and Subjective Norms on The Intention to Engage in Pro-Environmental Behavior, with Attitude Toward The Plastic Ban as A Moderating Variable - Nada Evada; Ihwan Susila; Imronudin Imronudin (PT. Publikasiku Academic Solution, 2026)
Plastic waste remains a critical environmental challenge, prompting the Indonesian government to implement various plastic bag restriction policies. However, regulations alone are insufficient without behavioral changes driven by individuals and their social environments. This study aimed to analyze the influence of environmental knowledge, consumer habits, and subjective norms on pro-environmental behavior intention and to examine the moderating role of attitude toward plastic bans in these relationships. A quantitative approach was employed involving respondents who were modern retail consumers in urban Indonesia and had been exposed to plastic restriction policies. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that environmental knowledge had a positive and significant effect on pro-environmental behavior intention. Consumer habits also exerted a positive and significant influence. Subjective norms emerged as the most dominant factor, demonstrating the highest t-statistic value. Conversely, attitude toward plastic bans did not have a significant direct effect on pro-environmental behavior intention. Moderation analysis revealed that attitude toward plastic bans significantly moderated the effects of consumer habits and subjective norms on pro-environmental behavior intention but did not moderate the effect of environmental knowledge. The R² value of 0.864 indicated that 86.4% of the variance in pro-environmental behavior intention was explained by all variables included in the model. This study extended the Theory of Planned Behavior (TPB) by integrating a public policy-based moderating variable, providing practical implications for designing more effective plastic reduction policies in Indonesia.